Membaca Makna di Balik Desain Uang Kertas Rupiah Emisi 2022: Kajian Semiotika Melalui Perspektif Charles Sanders Peirce - Ernawati Ernawati; Khusnul Khotimah (Pusat riset dan Inovasi Nasional, 2025)
The design of banknotes is not merely an aesthetic element but also holds symbolic meanings that reflect a nation's identity, history, and cultural diversity. This study analyzes the design of the 2022 Rupiah banknotes using Charles Sanders Peirce’s semiotic approach, which consists of icons, indexes, and symbols, through a qualitative descriptive method. The findings indicate that the visual elements in these banknotes function not only as a medium of exchange but also as a visual communication tool that strengthens nationalism and cultural awareness. National heroes, traditional dances, indigenous flora, and natural landscapes featured on each denomination carry both explicit and implicit meanings that represent Indonesia's historical and cultural values. Furthermore, the design differences between the 2016 and 2022 emissions, such as the use of more vivid colors, varied sizes, and enhanced security features, highlight the government's visual communication strategy to maintain authenticity and facilitate Rupiah identification. This study provides insights into how banknote design serves as an educational medium and a unifying tool for the nation through meaningful visual symbols.